Foundations of EU Network of Comprehensive Cancer Centers Successfully Laid - Jelenc, Marjetka; Albreht, Tit (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
European Network of Comprehensive Cancer Centers (EUNetCCC) will be established in Europe in accordance with the Europe's Beating Cancer Plan. The foundations for the network, including the professional, scientific, educational and administrative framework for a sustainable structure, were prepared as part of CraNE Joint Action (JA), which ended in 2024. EUNetCCC will help to ensure the quality of diagnostics, treatment, research and education in Europe. The goal of the EU Commission is that 90% of cancer patients have access to EUNetCCC by 2030. The main achievement of CraNE JA was the establishment of the leadership, management structure of the EUNetCCC. The set of standards for certification of centers, pilot networks for the treatment of lung cancer, and maturity model for self-assessment and further development of the CCC were developed. On these starting points is based EUnetCCC JA, which will establish the network with the start of CCC certification procedures.